Exploring the Effects of Using Smartphones for Teaching Secondary School Learners English Composition Writing - Alice Dhliwayo; Thuthukile Jita (Journal of Pedagogical and Teacher Professional Development, 2025)
There are well known requisites for  further studies after Ordinary Level in Zimbabwe that are negatively impacted by traditional pedagogical practices, giving rise to the need for new methods for mitigation. For Zimbabwean learners, a full O level certificate must include English language, yet it is the most failed subject. Through the lens of the theory of Network Society, this study explored the effects of integrating smartphones for technology integration on high school learners’ performance and affective learning in English composition writing. A quasi-experimental case study design with a three-step process was followed. In Step 1, a pre-test was administered to 104 purposively selected learners as well as a questionnaire on attitude. In Step 2, 52 learners became the control class and 52 the experimental class, who were subjected to smartphone-integration learning in English composition writing. Step 3 involved administering a post-test to both groups. Data was analysed using thematic analysis, ANOVA, ANCOVA and t-tests with results revealing that the experimental class developed positively affectively and in performance. The smartphone method improved performance regardless of gender. With an above 84% smartphone penetration and an information and communication technology (ICT) tools shortages in public schools. In line with these findings, teachers of English composition writing may adapt the smartphone for integration to improve learner performance.